Comprehensive Efforts to Accelerate Non-Communicable Disease Services in the Era of COVID-19 in Indonesia’s Suburban Area - Taher, Akmal; Gondhowiardjo, Soehartati A; Bachtiar, Adang; Prasetyo, Sabarinah; Pixelyne, Irene; Huang, Ficky; Ahmad, Rima Sumayyah (UI Scholars Hub, 2022)
The COVID-19 crisis has disrupted non-communicable disease (NCD) services in primary health care, and NCD is one of the comorbidities that increase mortality in COVID-19 patients. Efforts to accelerate NCD services were carried out with the focus on two programs: the development of integrated polyclinic NCD services and the training of community health workers (CHW) at the Tanara Community Health Center (CHC) in Banten. The development of a continuous team-based service system from the Pos Pembinaan Terpadu (Posbindu)/integrated service post to NCD services at the CHC was carried out for six months to improve the quality of human resources and help provide recommendations in the implementation of NCD services. At the end of the program, there was a 26.1% increase in the number of hypertension patients receiving treatment compared with the previous year, and there was a significant increase in the level of knowledge of CHWs after training and long-term mentoring (p < 0.001). Efforts to accelerate NCD services require support from all parties, and to ensure the continuity of these efforts, periodic monitoring and evaluation are necessary.